2019
DOI: 10.3390/ijerph16091619
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Tetanus Vaccination among Adult Immigrants: Findings from the Portuguese National Health Survey 2014

Abstract: Vaccination is an effective strategy to prevent tetanus, and in Portugal this service is provided free of charge. Despite this, immigrants reported lower tetanus vaccination coverage than did Portuguese natives. The objective of this study was to identify sociodemographic, migration-related, and access-to-care factors associated with tetanus vaccination coverage among adult immigrants, using data from the Portuguese National Health Survey 2014. For the sample of 1277 immigrants aged ≥18 years, we estimated sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 26 publications
(41 reference statements)
0
24
0
Order By: Relevance
“…A human health survey in Portugal investigated factors associated with tetanus vaccination in immigrants. Higher household income and older age were negatively associated with tetanus vaccination rates, while living in sparsely populated areas was positively associated [57]. This could be due to the fact that people in rural areas are involved in agricultural work and therefore have more contact with soil in which the tetanus-causing pathogen is usually located.…”
Section: Plos Onementioning
confidence: 99%
“…A human health survey in Portugal investigated factors associated with tetanus vaccination in immigrants. Higher household income and older age were negatively associated with tetanus vaccination rates, while living in sparsely populated areas was positively associated [57]. This could be due to the fact that people in rural areas are involved in agricultural work and therefore have more contact with soil in which the tetanus-causing pathogen is usually located.…”
Section: Plos Onementioning
confidence: 99%
“…Six (28,29,75,(79)(80)(81) out of eight studies found that under-vaccination was significantly associated with more recent migration to the host country (28,29,75,79,81) or lower acculturation with the host society (80). Other common predictors of under-vaccination included higher income (3 out of 4 studies; (41,45,85), being a refugee/asylum seeker (2/3 studies; (49, 81)), having not accessed healthcare in more than a year (2/2; (41, 45)), having no private health insurance (2/2; (41,45)) and region of residence (2/2; (28,45)). Specific familial characteristics, such as parental education level, difficulties speaking the host country language or larger family size were also associated with under-vaccination.…”
Section: Determinants Of Under-vaccination In Migrant Populationsmentioning
confidence: 99%
“…Poor HCP knowledge of migrants' entitlements to healthcare and vaccination guidelines (e.g., vaccination of individuals with incomplete/uncertain immunisation status) was highlighted, with instances of patients being wrongly refused access to primary care or not offered recommended catch-up vaccinations. (31,45,57,62) A French study of GPs found wide variation in vaccination practices for newly-arrived migrants with no vaccination record, with some GPs reluctant to revaccinate those with uncertain immunisation status due to concerns about reactogenicity. (58) There were also missed opportunities to vaccinate;…”
Section: Barriers and Facilitators To Vaccine Uptake In Migrant Populationsmentioning
confidence: 99%
See 2 more Smart Citations